The Effect of a Local Bacterial Isolates of Pseudomonas spp in Growth and Elements Nutrition Uptake of (Vinga sinesis) & (Rhaphanus stativus) - Habh, Asseel M.M.; Al-Jaleel Khalil, Mohammed A.; Alfili, Suhad Y.; Idan, Rami M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
An experiment was conducted to study the effect of four isolates of Pseudomonas spp. on the growth of two plants Radish & Cowpea and on the concentrations of macro elements & microelements . This experiment included two parts , the 1st. part included isolation and characterization of 4 isolates of Pseudomonas bacteria from local Iraqi soils Baghdad . The 2nd part included planting two plants Radish & Cowpea in plastic pots size 5Kg -soil in the green house Biology Dept. College of Science , after planting we added the isolates to the pots , and after 50 days, the growth parameters length , fresh and dry weight , percentage of germination were recorded , and the concentrations of macro elements Mg ,P ,K ,Fe, and Ca ,and microelements Zn ,Cl ,Mo ,Cu ,and Ba. The results showed that the bacterial isolates were effective in promoting the growth of two plants comparing with control plants , the concentrations of maco & microelements were increased in both plants after adding the bacteria to the plants. Results were analyzed statistically using the least significant difference and at the level of probability of 0.05.